Body MDCT in small animals : basic principles, technology, and clinical applications - Bertolini, Giovanna (Springer, 2017)
This book is an up-to-date, technically detailed yet easy-to-read reference book on current clinical applications of MDCT in small animals. It has been designed to serve as the reference book for all MDCT-users, such as veterinary radiologists, imaging technicians, oncologists, surgeons, and non-radiologist clinicians. Individual chapters on novel clinically important topics include applications in endocrinology, oncology, trauma, and cardiovascular CT, as well as sections on organ-specific pathologies and their CT characteristics. The book will also cover main domains of CT, such as thorax and the trauma imaging. Anatomy, clinical aspects, pathology, and CT signs are integrated to provide the reader with the basis for interpretation of MDCT findings. Many excellent 2D multiplanar and 3D figures illustrating typical CT findings of various conditions will serve as a clinical reference for the reader.- Resumé vydavatel
Keywords: veterinární radiografie; multidetektorová výpočetní tomografie; zájmová zvířata; veterinary radiography; multidetector computed tomography; pets; elektronické knihy; sborníky; electronic books; papers of several authors